Historical development of curricular transformation processes of technical education in Santa Fe, Argentina (1984-2005) (Itinerarios Educativos, 2020)
This article discusses some historical approximations to the development of the curricular transformation processes undergone by technical educationin Santa Fe province. An introduction is provided todescribe the curricular construction processes in technical education throughout history, delving deeply intoa more delimited period from 1984 to 2005 approximately. The analysis and description of these processes are framed into the documents and laws thataccount for current regulations on technical education.
Keywords: technical education; Santa Fe province; curriculum transformation; education and work; curriculum